2020
DOI: 10.4274/tjps.21033
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Evaluation of Transdermal Microneedles for a Recombinant Human Keratinocyte Growth Factor

Abstract: Objectives: Microneedles transdermal patches is the combination between hypodermic needles and transdermal patches to overcome the individual limitations of both injections and patches. The objective of this study was to design a minimally invasive biodegradable polymeric recombinant human keratinocyte growth factor (rHuKGF) microneedles array and evaluate the prepared biodegradable microneedles using in-vitro techniques. Materials and Method: Biodegradable polymeric microneedles arrays were fabricated out of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Therefore, the authors ascribed the higher amount of proteins to the higher surface area of larger AuNSs. Furthermore, Chellathurai et al [34] reported a direct correlation between NP size and protein adsorption, as they determined that the small NP size and the hydrophilic surfaces inhibit the formation of a large amount of protein adsorption.…”
Section: The Effect Of Np Sizementioning
confidence: 99%
“…Therefore, the authors ascribed the higher amount of proteins to the higher surface area of larger AuNSs. Furthermore, Chellathurai et al [34] reported a direct correlation between NP size and protein adsorption, as they determined that the small NP size and the hydrophilic surfaces inhibit the formation of a large amount of protein adsorption.…”
Section: The Effect Of Np Sizementioning
confidence: 99%
“…Due to vortexing/stirring to ensure uniform drug distribution and dissolution, despite sonication of drug in PVP solution, significant bubble generation is typical, and it is important to ensure complete degassing by vacuuming during fabrication as bubbles could affect needle integrity, form, and drug loading [33]. It could also influence drug release properties [31].…”
Section: Patch Optimizationmentioning
confidence: 99%
“…They are expected to shorten drug delivery time and hence onset of action. Moreover, safety issues including needle breakage in skin and the need for the disposal of needles post usage into the environment which are typical of solid type MNs are evaded [33][34][35]. Their typical less complex fabrication requirements are expected to be more adaptable to the large-scale use of NAL and the clinical and commercial success of rapidly dissolving NAL MNs are thus foreseen.…”
Section: Introductionmentioning
confidence: 99%
“…Although polypeptides are used to treat various ailments and diseases, major drawbacks are their in vitro and in vivo stability. Currently, researchers overcome this problem by developing various novel drug delivery systems (Kumar et al 2018;Kumar et al 2019;Chellathurai et al 2021;Tee et al 2021). One of the smartest approaches that is predicted is converting these polypeptides into cyclic peptides, but their pharmacological properties and stability need to be proven once again after conversion.…”
Section: Introductionmentioning
confidence: 99%